2015
DOI: 10.1111/mec.13025
|View full text |Cite
|
Sign up to set email alerts
|

Life‐stage differences in spatial genetic structure in an irruptive forest insect: implications for dispersal and spatial synchrony

Abstract: Dispersal determines the flux of individuals, energy and information and is therefore a key determinant of ecological and evolutionary dynamics. Yet, it remains difficult to quantify its importance relative to other factors. This is particularly true in cyclic populations in which demography, drift and dispersal contribute to spatio-temporal variability in genetic structure. Improved understanding of how dispersal influences spatial genetic structure is needed to disentangle the multiple processes that give ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 77 publications
(152 reference statements)
1
33
1
Order By: Relevance
“…() demonstrated low levels of genetic differentiation among O. brumata populations across a study region of comparable spatial extent to the present study in the Orkney islands and suggested that this was due to high gene flow resulting from dispersal of ballooning larvae. Genetic evidence for high rates of gene flow and dispersal across distances of tens to hundreds of kilometres has recently also been obtained for two other cyclic lepidopteran defoliators: the western tent caterpillar ( Malacosoma californicum pluviale Packard) (Franklin, Myers, & Cory, ) and the eastern spruce budworm ( Choristoneura fumiferana Clemens) (James et al., ). In both cases, the authors suggested that dispersal plays an important role in synchronizing populations at the spatial scales considered.…”
Section: Discussionmentioning
confidence: 96%
“…() demonstrated low levels of genetic differentiation among O. brumata populations across a study region of comparable spatial extent to the present study in the Orkney islands and suggested that this was due to high gene flow resulting from dispersal of ballooning larvae. Genetic evidence for high rates of gene flow and dispersal across distances of tens to hundreds of kilometres has recently also been obtained for two other cyclic lepidopteran defoliators: the western tent caterpillar ( Malacosoma californicum pluviale Packard) (Franklin, Myers, & Cory, ) and the eastern spruce budworm ( Choristoneura fumiferana Clemens) (James et al., ). In both cases, the authors suggested that dispersal plays an important role in synchronizing populations at the spatial scales considered.…”
Section: Discussionmentioning
confidence: 96%
“…In this case, mass flights of moths have been observed [68]. Geneflow among populations is high and genetic structure low [69].…”
Section: A Lack Of Genetic Differentiation: An Indicator Of Dispersalmentioning
confidence: 95%
“…Larval-host interactions appear to be strongly tied to speciation in the spruce budworm species complex (Fagua, Condamine, Brunet, et al, 2018;Fagua, Condamine, Dombroskie, et al, 2018). James et al (2015) used microsatellite markers to study the population genetics of spruce budworm within the Border Lakes region of Ontario and Minnesota to detect dispersal by comparing larvae (residents) to adults captured in pheromone traps (potential migrants). James et al (2015) used microsatellite markers to study the population genetics of spruce budworm within the Border Lakes region of Ontario and Minnesota to detect dispersal by comparing larvae (residents) to adults captured in pheromone traps (potential migrants).…”
Section: Introductionmentioning
confidence: 99%
“…For C. fumiferana, May, Leonard, and Vadas (1977) studied electrophoretic variation of loci in spruce budworm collected in northern Maine and found no significant population differentiation. James et al (2015) used microsatellite markers to study the population genetics of spruce budworm within the Border Lakes region of Ontario and Minnesota to detect dispersal by comparing larvae (residents) to adults captured in pheromone traps (potential migrants). Recently, Larroque et al (2019) used SNP markers to detect spatiotemporal variation in population genetic structure during spruce budworm population outbreaks in Quebec.…”
Section: Introductionmentioning
confidence: 99%